OPTIMALISASI SARANA PENGANGKUTAN SAMPAH DI DESA BLANG KRUENG ACEH BESAR - Irmayani, Irmayani; Syahril, Syahril; Hidjrawan, Yusi (Universitas Teuku Umar, 2019)
Waste management aims to protect clean and healthy environment. Handling of waste problems in Blang Krueng area still has many obstacles. Most of the locations of waste disposal in Blang Krueng area do not meet health requirements. People do not yet have waste dumping. This is due to the unavailability of waste transportation facilities. In addition, in order to overcome this waste, people often burn the wastes. However, it can cause air pollution. Thus, this research is expected to optimize waste transportation facilities based on the number of ritations by using waste generation data in the area. The last hope of course the cleanliness Â in Blang Krueng area.